KASUS DISTRIBUSI DAN PENGGUNAAN FORMALIN DALAM PENGAWETAN KOMODITI IKAN LAUT SEGAR (STUDI KASUS DI KOTA BANDAR LAMPUNG) [Formaldehyde Distribution and Using for Preserving Fresh Fish (A Case Study in Bandar Lampung City)] - Dias Yusdianson Girsang; Azhari Rangga; Susilawati Susilawati (Jurnal Teknologi & Industri Hasil Pertanian, 2014)
The purpose of this study was to identify the presence of formaldehyde in some fresh fish commodities and to trace formaldehyde distribution in Bandar Lampung City. The  formadelhyde tests were done  on the storage water of fresh fish samples. The study conducted in July to October 2013 was devided in two stages: a survey to fill out a questionnaire to a number of respondents, followed by sampling some storage water of fresh fish to be tested in the laboratory.  The tests were  carried out on 52 sampling points taken from the fishing boats in the fishing landing port (17 boats), fish supplier car from outside Bandar Lampung (6 cars) as well as some